Risk stratification of advanced colorectal neoplasia after baseline colonoscopy: Cohort study of 17 Japanese community practices - Shono, Takashi (Dig Endosc, 2019)
BACKGROUND AND AIM: In Japan, risk stratification after baseline colonoscopy is not widely accepted. We investigated the findings of baseline colonoscopies at 17 community practices and evaluated the risk of the incidence of advanced neoplasia over a 5‐year period. METHODS: This retrospective cohort study enrolled 3115 subjects over 40 years of age who underwent baseline colonoscopies and had at least one repeated colonoscopy within 5 years. Each group was classified based on the endoscopic findings of the baseline colonoscopy: no neoplasia/diminutive polyp <5 mm (N/D); small adenoma <10 mm; advanced adenoma; invasive cancer, respectively. We examined the incidence of advanced neoplasia during these 5 years and investigated the relationship between the surveillance colonoscopy and newly detected advanced neoplasia. RESULTS: The small adenoma group did not show any significant increased risk as compared to the N/D group (hazard ratio [HR]: 0.799. 95% CI 0.442–1.443). There was a significantly increased risk in the advanced adenoma and invasive cancer groups (HR: 4.996, 95% CI 2.940–8.491, HR: 3.737, 95% CI 1.309–10.666). Cancer incidences during the study period were 0.18% in the N/D group, and 1.9% in the invasive cancer group, respectively. Undergoing surveillance colonoscopies twice within 5 years decreased the risk of advanced neoplasia. CONCLUSIONS: There was a close relationship between the endoscopic findings of baseline colonoscopies and subsequent advanced neoplasia development. Risk stratification for advanced neoplasia based on the baseline findings can serve as a useful index for determining the optimal interval and frequency of colonoscopies over a 5‐year period.